Reforming the Urban Water System in Santiago, Chile - Shirley, Mary M.; Xu, L. Colin; Zuluaga, Ana Maria (World Bank, Washington, DC, 2015)
In the late 1980s, Chile planned to privatize Santiago's sanitary works enterprise (EMOS) but instead reformed it under public ownership. It did so through a regulatory framework that mimicked the design of a concession with a private utility, setting tariffs that ensured at least a seven percent return on assets, creating a neutral regulator independent of ministry intervention, and giving EMOS the right to appeal the regulator's tariff decisions. This reform of Santiago's water system is often cited as a case of successful reform under public management. Comparing a comprehensive measure of welfare with a counterfactual example, the authors show surprisingly large gains from Santiago's reform, given the relatively good initial conditions. (The gains accrued largely to government and employees, but consumers benefited from improved service and coverage). Why did reform in Santiago improve water system performance, when similar reform attempts under public management in other countries failed? 1) Chile has a long tradition of private water rights, shaped by early recognition that water is a scarce and tradable private good. 2) The reformed regulatory framework was designed to attract private investors to the water system and to motivate them to operate efficiently and expand the system. 3) Chile's unique electoral institutions sustained this framework under state operation after democracy was restored. 4) Chile's strong bureaucratic norms and institutions (permitting little corruption), combined with Santiago's relatively low-cost water system, permitted prices that effectively increased quasi-rents for investing in the system while minimizing the risk of inefficiency or monopoly rents. The authors also address the question of why EMOS was reformed but not privatized, and what the costs of not privatizing were. The system was privatized in 1999, but the changes from privatization are likely to be less significant than those introduced in 1989-90.